Application of the PEGDE modified silk fibroin membrane to an amperometric glucose biosensor - Moorish P. (2014)
Stable silk fibroin (SF) membranes were prepared by modifying SF with polyethylene glycol diglycidyl ether (PEGDE) for use as enzyme immobilizing matrix. Morphology, structure, and water solubility of the modified silk fibroin (MSF) membrane were investigated. SEM images revealed greater porosity in the MSF membranes. IR spectra confirmed the predominant β-sheet conformation when the PEGDE was greater than 4%. In addition, the MSF membranes were highly insoluble within the pH range 4 10. An amperometric glucose biosensor was initially constructed using glucose oxidase (GOx) immobilized on the MSF membrane, coupled to a Prussian Blue (PB) deposited Au electrode. The response characteristics of the biosensors based on the GOx immobilized onto the 4% and 8% PEGDE modified SF membranes (4P-MSF and 8P-MSF) and the methanol treated SF membrane (MT-SF) were investigated. Amperometric measurements at the applied potential of 0.0 V demonstrated that the glucose biosensor based on the GOx immobilized onto the 4P-MSF membrane exhibited high sensitivity to glucose with a short response time, less than 3 s. Moreover, the stability of the biosensors based on the 4P-MSF membranes was better than those based on the MT-SF membrane after 2 weeks of storage in a phosphate buffer of pH 7.0 at 4 °C. These fundamental electroanalytical features of the sensor are therefore expected to be useful in biosensor application © 2008 Trans Tech Publications, Switzerland.